No Association Between G1246A Polymorphism in HCRTR2 Gene and Risk of Cluster Headache: Evidence From an Updated Meta-Analysis of Observational Studies - Yang, Jiao; Yu, Si-yi; Yang, Jie; Kong, Jing; Liang, Fan-rong; Lv, Zheng-tao (Frontiers in Genetics, 2020)
Background: The hypocretin receptor 2 (HCRTR2) gene may play a pathological role in cluster headache (CH). However, the conclusions of published reports on the relationship between the G1246A polymorphism (rs2653349) in HCRTR2 gene and risk of CH remain controversial. This study was conducted to comprehensively assess the current evidence on the asso¬ciation between G1246A polymorphism (rs2653349) in HCRTR2 gene and risk of CH. Materials and methods: Four electronic databases, including PubMed, EMBASE, ISI Web of Science and CNKI were systematically searched to identify relevant observational articles published before August 2020.Summary odds ratio and corresponding 95% CI were calculated to evaluate the association between G1246A polymorphism in HCRTR2 gene and risk of CH under five different genetic models. Methodological quality was assessed based on the Newcastle–Ottawa Scale (NOS). Subgroups and sensitivity analyses were performed using the RevMan 5.3 software. Publication bias was evaluated by Egger’s and Begg’s tests. Meta-regression was carried out by residual (restricted) maximum likelihood (REML) Results: Eight observation studies containing 1,964 patients with CH and 3,161 healthy controls were obtained for the meta-analysis. According to the NOS, the included studies achieved an average of 6.4stars for methodological quality assessment. The pooled data didn’t support the association between G1246A polymorphism in HCRTR2 gene and CH vulnerability in the overall population (OR: 0.85, 95%CI 0.69, 1.03; p=0.10). Subgroup-analysis by ethnicity showed no significant association between G1246A and CH in either Caucasian (OR: 0.89, 95%CI 0.77, 1.01; p=0.08) or Asian (OR: 1.65, 95%CI 0.80, 3.41; p=0.18). The leave-one-out sensitivity analysis confirmed the robustness of the conclusion. Meta- regression analysis showed that chronological order of publication appeared to significantly associated with the heterogeneity (t=2.47, p=0.039; residual I2=0%, adjusted R2=100%). Conclusion: Based on the findings of our present study, the G1246A polymorphism in HCRTR2 did not appear to be associated with CH predisposition among either Asian or Caucasian population.